Palma forrageira e gérmen integral extragordo de milho em dietas para cabras em lactação : perfil de ácidos graxos - CORRÊA, Agni Martins Nunes (2022)
Recent research has found that forage cactus (Opuntia stricta [Haw], Haw) has a unique characteristic of reducing the C18:0 levels of milk from cows fed cactus associated with vegetable oil. The objective of the present study was to evaluate the effects of partial replacement of elephant grass (Pennisetum purpuream, Schum) by forage cactus and total corn ground with extra-fat whole corn germ (GINEX) on the fatty acid profile of goat milk fat. The experiment was carried out in the goat farming sector of the Animal Science Department (DZ), at the Federal Rural University of Pernambuco (UFRPE), in the city of Recife. Twelve lactating Saanen goats, multiparous, with average body weight of 54 ± 5.0 kg, initial production of 2.1 kg of milk/day and average lactation period of 45 ± 7 days were used. The animals were distributed in three simultaneous 4 x 4 Latin squares according to milk production and assigned to four treatments in a 2 x 2 factorial arrangement, corresponding to two energy sources (corn or GINEX) and the presence or not of forage cactus Mexican Elephant Ear (FCMEE). Data were analyzed using the SAS PROC MIXED procedure. There was an increase (P = 0.03) in milk fat contents with the use of GINEX as an energy source. The association of palm and GINEX provided a significant increase (P< 0.001) in the CLA concentration cis-9, trans-11 (1.96 g/100 g) and C18:1 trans-11 (1.96 g/100 g) in the goat milk fat. In parallel, the use of cactus reduced the levels of C18:0. When palm was associated with GINEX, there was a reduction in C16:0 (20.37 g/100 g). The use of diets containing GINEX forage cactus is recommended as it increases the nutraceutical properties of goat milk.